A Journey Through 100 Years of Vestibular Schwannoma Surgery at Mayo Clinic: A Historical Illustrative Case Series. Issue 10 (December 2020) - Huang, Alice E.; Marinelli, John P.; Link, Michael J.; Boes, Christopher J.; Carlson, Matthew L.
Abstract : N/A: The present state of vestibular schwannoma (VS) management is the product of over a century of technical progress by revolutionary surgeons who transformed a once perilous operation. At the beginning of the 1900s, patients who did not succumb to their disease were treated exclusively with surgery, which itself was almost assuredly devastating. Through the pioneering work of surgeons such as Harvey Cushing, Walter Dandy, William House, and others, safer surgical approaches were established with concurrent advances in neuromonitoring, neuroanesthesia, radiology, and adoption of the operating microscope. Owing to refinements in radiosurgical treatment and a greater understanding of the natural history of disease, there has been a dramatic shift toward more conservative management in recent years. For more than 100 years, the Mayo Clinic in Rochester, MN, has maintained an active and uninterrupted VS practice with activities that are well documented and preserved through the Mayo Clinic historical archives. We herein report representative early cases to illustrate the fascinating evolution in VS surgery over the past century at a single-tertiary referral center. Original clinical, imaging, pathology, and operative reports are presented from each era of management. To accurately portray the medical context of each era, antiquated terminology is intentionally preserved as originally transcribed.